Effects of Suryanamaskar on Cardio Vascular and Respiratory Parameters in School Students - Sivapriya D V2, Shyamala Thirumeni3, Sasi Kumar A1*, (Recent Research in Science and Technology, 2011)
Back ground: Modern medical science has started to study the effects of suryanamaskar and yogic techniques. With increasing scientific research in suryanamaskar and yoga, its therapeutic aspects are explored in wide angle. In yoga the sun is represented by surya nadi, the pranic channel which carries the vital life- giving force. Suryanamaskar is the combination of asana and pranayama. Suryanamaskar has been integrated into physical education in many public and private schools across the country. The ultimate goal is to improve the physical health and increase the quantity of sportsmen with effective cardio-respiratory efficiency. Methods : This study was designed to evaluate the effects of a 45 days daily practice of suryanamaskar on blood pressure(BP), heart rate(HR), respiratory rate (RR), forced vital capacity(FVC) and peak expiratory flow rate (PEFR) in school students of both sexes.115 school students aged 10 to 14 years were recruited for the study. The participants were trained to perform suryanamaskar for 45 days study period. The cardio vascular and respiratory parameters BP, HR, RR, FVC and PEFR were measured before and after practice of suryanamaskar. Results: The results showed that the Systolic blood pressure, PEFR and FVC increased significantly and RR, HR and diastolic blood pressure decreased significantly after the practice of suryanamaskar. Conclusion: The beneficial effects of suryanamaskar can be applied to all schools to improve the physical health and sports activities of the students.